IL-21 Rescues the Defect of IL-10-Producing Regulatory B Cells and Improves Allergic Asthma in DOCK8 Deficient Mice - Jiang, Jinqiu; Qin, Tao; Zhang, Liang; Liu, Qiao; Wu, Jiabin; Dai, Rongxin; Zhou, Lina; Zhao, Qin; Luo, Xiaoyan; Wang, Hua; Zhao, Xiaodong (Frontiers in Immunology, 2021)
Mutations in human DOCK8 cause a combined immunodeficiency syndrome characterized by allergic diseases such as asthma and food allergy. However, the underlying mechanism is unclear. Regulatory B (Breg) cells that produce IL-10 exert potent immunosuppressive functions in patients with allergic and autoimmune disorders. DOCK8-deficient B cells show diminished responses to TLR9 signaling, suggesting a possible defect in IL-10-producing Breg cells in those with DOCK8 deficiency, which may contribute to allergies. Here, we isolated peripheral blood mononuclear cells from DOCK8-deficient patients and generated a Dock8 KO mouse model to study the effect of DOCK8 deficiency on Breg cells. DOCK8-deficient patients and Dock8 KO mice harbored quantitative and qualitative defects in IL-10-producing Breg cells; these defects were caused by abnormal Dock8-/- CD4+ T cells. We found that recombinant murine (rm)IL-21 restored the function of Bregs both in vitro and in Dock8 KO mice, leading to reduced inflammatory cell infiltration of the lungs in a murine asthma model. Overall, the results provide new insight into the potential design of Breg-based or IL-21-based therapeutic strategies for allergic diseases, including asthma associated with DOCK8 deficiency.